1997
DOI: 10.1212/wnl.48.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Very Old Women at Highest Risk of Dementia and Alzheimer's Disease

Abstract: (1) The incidence of dementia increases with age, even in the oldest age groups; (2) women have a higher risk of developing dementia than men, especially at very old ages; (3) this pattern is mainly due to the age and gender distribution of Alzheimer's disease, rather than vascular dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
341
4
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 501 publications
(378 citation statements)
references
References 18 publications
30
341
4
3
Order By: Relevance
“…Some population-based studies have found the incidence of Alzheimer's disease to be higher among women, 30,[39][40][41] while others have not, 42,44,46 Devenand et al, in a smaller and slightly differently defined cohort of elderly subjects with mild memory impairment found no association between female sex and the development of dementia. 15 We confirm this finding in our cohort.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some population-based studies have found the incidence of Alzheimer's disease to be higher among women, 30,[39][40][41] while others have not, 42,44,46 Devenand et al, in a smaller and slightly differently defined cohort of elderly subjects with mild memory impairment found no association between female sex and the development of dementia. 15 We confirm this finding in our cohort.…”
Section: Discussionmentioning
confidence: 97%
“…The risk factors that derive from the literature include age, 29,30 a family history of dementia, 31 history of head injury, 32,33 depression, 34,35 as well as low pre-morbid intelligence and education. [36][37][38] Female gender has been noted to be a risk factor for dementia in a number of studies, 30,[39][40][41] although this has not been found in others. [42][43][44][45][46] The onset of subjective memory complaints may be a risk factor for development of subsequent cognitive decline.…”
Section: Clinical Risk Factors For Development Of Dementia and Admentioning
confidence: 99%
“…The risk of the development of any form of dementia is reported to be approximately twice as high in females as in males and the risk of Alzheimer's disease is as much as three times higher in females 8 . Numerous other studies report the incidence rates of dementia and AD as the number of persons per year.…”
Section: Prevalencementioning
confidence: 99%
“…The study population was derived from the Kungsholmen project, which is a population-based prospective study on ageing and dementia as fully described elsewhere [26,27]. In brief, all registered inhabitants who were living in the Kungsholmen district of Stockholm, Sweden, and were aged ≥75 years on 1 October 1987 were initially invited to participate in the project.…”
Section: Study Populationmentioning
confidence: 99%
“…Baseline data collection Data on age, sex and education were collected from participants at baseline following standardised protocols [26,27]. Education was measured by the maximum years of formal schooling, and was dichotomised (≥8 vs <8 years) according to our previous study [29].…”
Section: Study Populationmentioning
confidence: 99%